2013
DOI: 10.18433/j3788x
|View full text |Cite
|
Sign up to set email alerts
|

Light-to-Moderate Ethanol Feeding Augments AMPK-α Phosphorylation and Attenuates SREBP-1 Expression in the Liver of Rats

Abstract: Purpose: Fatty liver disease, a hepatic manifestation of metabolic syndrome, is one of the major causes of chronic liver diseases. Epidemiological studies suggest that regular light-to-moderate ethanol consumption lowers the risk of developing metabolic disorders including dislipidemia, insulin resistance, type 2 diabetes and fatty liver disease. However, the mechanism(s) of the protective effect of light-to-moderate ethanol consumption on the liver remains unknown. Methods: In the present study, we investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 59 publications
1
4
0
Order By: Relevance
“…AMPK plays a key role in regulating the effects of ethanol on hepatic SREBP-1 activation, fatty acid metabolism, and the development of alcoholic fatty liver [ 32 ]. Increased expression of AMPK and decreased expression of SREBP-1 as observed are in agreement with the literature linking AMPK and SREBP-1 [ 38 , 39 , 40 , 41 ]. SREBP-2 regulates the genes of cholesterol biosynthesis and metabolism in hepatocytes [ 26 , 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…AMPK plays a key role in regulating the effects of ethanol on hepatic SREBP-1 activation, fatty acid metabolism, and the development of alcoholic fatty liver [ 32 ]. Increased expression of AMPK and decreased expression of SREBP-1 as observed are in agreement with the literature linking AMPK and SREBP-1 [ 38 , 39 , 40 , 41 ]. SREBP-2 regulates the genes of cholesterol biosynthesis and metabolism in hepatocytes [ 26 , 42 ].…”
Section: Discussionsupporting
confidence: 92%
“…38 These contradictory results may be due to different pathological degrees of ALD. 39 The present results showed that chronic alcohol consumption had no obvious effect on hepatic fatty acid oxidation, but it significantly increased TG synthesis genes (Dgat1). PlsEtn, PlsCho and NAC treatment efficiently inhibited fatty acid uptake and TG synthesis.…”
Section: Discussionmentioning
confidence: 48%
“…With respect to alcohol's effect on hepatic DNL, there is no consensus in the literature regarding this important contributor to hepatic TG levels. While it has been reported by You et al that alcohol increases SREBP1c expression with resultant effects on hepatic fatty acid synthesis ( 26,27 ), others have recently reported that alcohol consumption decreases SREBP1c expression ( 28 ). Our results are in agreement with Tijburg et al and Venkatesan et al, who conducted Although G6pc (glucose synthesis) expression was not signifi cantly different in any group, Pepck expression was signifi cantly higher in Cd36 Ϫ / Ϫ versus WT mice, suggesting increased gluconeogenesis in these animals.…”
Section: Evidence Of Dysregulated Hepatic Lipid and Glucose Metabolismentioning
confidence: 95%